The genome-wide transcription response underlying the dorsal processes and dorsal setae of the body in Dasyaphis mirabilis (Aphididae: Calaphidinae). (2nd January 2019) - Zhang, Rong-Jiao; Chen, Jing; Jiang, Li-Yun; Qiao, Ge-Xia
Abstract: Dasyaphis mirabilis is capable of producing short or long dorsal processes and dorsal setae in nature. However, the molecular genetic mechanisms underlying the induction of the short or long dorsal processes and dorsal setae in some species remain unknown. Therefore, we performed a comparative analysis of transcriptional profiling among the short and long morphs and revealed that the expression of some co-activators, such as β - catenin, Runx1, Runx3, Hes1, Delta - like 1, Hairless, Smad4, Comp, Egfr, Fgfr2, Bmp2, Noggin, Iftl72, Msx2, and Med1, and co-repressed genes, such as Groucho, are consistent with changes in the expression of Wnt, Notch, Hh, TGF-β, MAPK and JAK-STAT signalling pathways in the dorsal processes and dorsal setae development. Moreover, our results also provide a model to explain the molecular adaptive mechanisms that environmental changes effect on the aphids, and lead to dorsal processes and dorsal setae development in D. mirabilis, and add a unique and significant insight into the molecular genetic mechanisms underlying the dorsal processes and dorsal setae in aphids.